2(5-3x)=4(x+2)-4(4-5x)7

Simple and best practice solution for 2(5-3x)=4(x+2)-4(4-5x)7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5-3x)=4(x+2)-4(4-5x)7 equation:



2(5-3x)=4(x+2)-4(4-5x)7
We move all terms to the left:
2(5-3x)-(4(x+2)-4(4-5x)7)=0
We add all the numbers together, and all the variables
2(-3x+5)-(4(x+2)-4(-5x+4)7)=0
We multiply parentheses
-6x-(4(x+2)-4(-5x+4)7)+10=0
We calculate terms in parentheses: -(4(x+2)-4(-5x+4)7), so:
4(x+2)-4(-5x+4)7
We multiply parentheses
4x+140x+8-112
We add all the numbers together, and all the variables
144x-104
Back to the equation:
-(144x-104)
We get rid of parentheses
-6x-144x+104+10=0
We add all the numbers together, and all the variables
-150x+114=0
We move all terms containing x to the left, all other terms to the right
-150x=-114
x=-114/-150
x=19/25

See similar equations:

| 2.3a+1.5=56 | | z-17=17 | | 8x-2=-15 | | 120+32+x=180 | | 3(y-2)+1=2(y-3)+(y+1 | | z+19=21 | | 5.4=3.3-3x | | -15=8x-2 | | 90-2x-3+10x-17=180 | | 2x-2(-x+11)=-10 | | 2x-2(x+11)=-10 | | 756+34x=246 | | 1.2n=48 | | 2x-2(x-11)=-10 | | -4x-(-6)=30 | | 11v+5=27 | | 7-7n=8(1-n)+6 | | 21^2+7h=0 | | 5+2v=-19 | | 1.5x-3=33 | | 3x+57=13x-3= | | Y=3.5x-70.5 | | 12+x=3(3-2) | | 2y-1.6=4 | | y=3.5-70.5 | | 2x+1=4x-23 | | x+18+4x=2x–14 | | -4x-(-6)=22 | | 21^2=7h | | x+2(5)=13 | | -5(p-2)=-25 | | 3+3a=-1+3a+4 |

Equations solver categories